Organised crime , violence and development (2016)
It is increasingly recognised in the international aid community that organised crime hinders inclusive and sustainable development in many ways. Today’s universe of organised criminal activities and of the individuals, groups and networks involved in them is virtually infinite. Spanning the whole globe, organised criminal operations range from illegal protection economies and extortion rackets to cybercrime, oil theft, money laundering, counterfeiting, maritime piracy and the trafficking and/or smuggling of illicit drugs, humans, firearms and wildlife.